2017
DOI: 10.1016/j.fusengdes.2017.05.120
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of flow velocity during turbulent natural convection in nanofluids

Abstract: Increased cooling performance is eagerly required for many cutting edge engineering and industrial technologies. Nanofluids have attracted considerable interest due to their potential to enhance the thermal performance of conventional heat transfer fluids. However, heat transfer in nanofluids is a controversial research theme, since there is yet no conclusive answer to explain the underlying heat transfer mechanisms. This study investigates the physics behind the heat transfer behavior of Al2O3–H2O nanofluids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…It is noted that the reported data are mean values out of 12 experiments (four experiments per plane), while the methodology for the heat transfer calculations is similar with that reported in previous work by the authors [2]. By comparing the general heat transfer, as expressed with the Nu, no change is observed within the experimental uncertainty between water and nanofluids, thus verifying earlier PIV experiments conducted in a single plane close to the centre of the cubic RB cell under three different Ra [44].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It is noted that the reported data are mean values out of 12 experiments (four experiments per plane), while the methodology for the heat transfer calculations is similar with that reported in previous work by the authors [2]. By comparing the general heat transfer, as expressed with the Nu, no change is observed within the experimental uncertainty between water and nanofluids, thus verifying earlier PIV experiments conducted in a single plane close to the centre of the cubic RB cell under three different Ra [44].…”
Section: Resultssupporting
confidence: 88%
“…Following earlier findings [44], it is reconfirmed that the maximum temporally averaged absolute velocity V j j avgÀmax , the spatially and temporally averaged absolute velocity V j j avg and the temporally and spatially averaged standard deviation of the turbulent velocity fluctuations Stdev are consistently higher for nanofluids than for DI water in the field of view. Additionally, it is demonstrated that this trend is consistent in all three planes, with the maximum difference between the velocity characteristics for DI water and nanofluid taking place at an absolute distance z of 4 ± 1 mm (front plane) from the central plane.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Interior boundaries were set with a continuity condition. Natural convective heat transfer was assumed small with a velocity component of 0.1 mm/s in the z-direction [27]. Mesh was kept the same as in the acoustic models.…”
Section: Models Equations and Conditionsmentioning
confidence: 99%
“…In this model, it was omitted the effect of agitation produced by the ultrasound radiation force that could act as an external force convection and should permit a more distributed heat. Although nature convection was included based on [27], the effect of acoustic agitation should be more significant. Therefore, real-temperature increments in the dish produced by ultrasound absorption should be smaller and more uniform than those shown in Figure 4 and can be comparable to the measured increments of 0.3 • C reported by [13].…”
Section: Models and Measurements For Setup Validationmentioning
confidence: 99%